La problemática de los nuevos derechos humanos - Clifford Bob. (Colombia Internacional, 2009)
Why are certain problems recognized as human rights issues, while others are not? This article focuses on the political strategies through which marginalized groups transform long standing domestic grievances into internationally-recognized human rights claims. Highlighting the interacting roles of aggrieved local groups, powerful gatekeepers in international human rights organizations, and state and civil society opponents, the article develops a four-stage model for the development of new human rights. The article also challenges constructivist theories about the formation of international norms development.